The Bible knowledge commentary an exposition of the Scriptures - Walvoord, John Flipse, 1910-; Zuck, Roy B.; Dallas Theological Seminary (Wheaton, IL Victor, 1985)
Contents : v. 1 : Old Testment. Includes bibliographical references.
Keywords: Bible. O.T. -- commentaries